2014
DOI: 10.1176/appi.ps.201400028
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid Expenditures on Psychotropic Medications for Maltreated Children: A Study of 36 States

Abstract: Objective Children with histories of abuse or neglect are the most expensive child population to insure for their mental health needs. This paper quantifies the magnitude of Medicaid expenditures incurred on the purchase of psychotropic drugs for these children. Methods Child participants (N=4445) in the National Survey of Child and Adolescent Well-Being (NSCAW) – consisting of children investigated for suspected abuse and neglect – were linked to their Medicaid claims from 36 states. Expenditures on psychot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…6,7 Children and adolescents involved with the child welfare system are 2 to 3 times more likely to be treated with psychotropic medication compared with those without such involvement. 8,9 In addition, 33% of all foster children are prescribed a psychotropic medication. Among Medicaid-eligible children, foster children are approximately 4 times more likely to be prescribed a second-generation antipsychotic than children not in foster care, 10 with 10% of foster children receiving 3 or more psychotropic medications at any given time.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Children and adolescents involved with the child welfare system are 2 to 3 times more likely to be treated with psychotropic medication compared with those without such involvement. 8,9 In addition, 33% of all foster children are prescribed a psychotropic medication. Among Medicaid-eligible children, foster children are approximately 4 times more likely to be prescribed a second-generation antipsychotic than children not in foster care, 10 with 10% of foster children receiving 3 or more psychotropic medications at any given time.…”
Section: Introductionmentioning
confidence: 99%
“…This study is unique from much of the past work done in this area for two related reasons: (1) It makes comparisons between two groups where one received an experimental intervention, and as such, (2) It makes comparisons between groups of children in which both groups have been exposed to maltreatment. Many past studies have been designed to investigate the effects of victimization vs. non-victimization (e.g., Raghavan et al, 2014;Florence et al, 2013). For this reason, comparisons between the results of this study and past work that did not involve study groups where the entire sample was exposed to maltreatment are limited in their ability to draw broader conclusions.…”
Section: How the Between-group Differences In Utilization Finding Commentioning
confidence: 94%
“…These findings may also be placed in context alongside the work described in Raghavan, Brown, Allaire, Garfield, & Ross (2014), which examined Medicaid expenditures on psychotropic medications for children who had been the victim of maltreatment. They found that children who had been the identified victim on a CPS case had twice the odds of receiving any psychotropic drug prescription, and $190 higher mean annual expenditures on psychotropic drugs than PSM-matched children who were never victims.…”
Section: How the Between-group Differences In Utilization Finding Commentioning
confidence: 98%
See 2 more Smart Citations